The Role Of Information And Educational Activity In The Formation Of Patriotic Qualities In Military Servants (Eurasian Research Bulletin, 2024)
In this article, the main goal of information and educational activities in the formation of patriotic qualities in military personnel is to strengthen the belief in the necessity and importance of armed defense of the homeland, to form a sense of responsibility for the fate of the army in every military personnel, to maintain high combat readiness, military discipline and legislation. , practical proposals and considerations aimed at strengthening the confidence of military personnel in the necessity and importance of armed defense of the homeland have been reflected.